Blood Pressure Circadian Variation, Cognition and Brain Imaging in 90+ Year-Olds - Paganini-Hill, Annlia; Bryant, Natalie; Corrada, Maria M.; Greenia, Dana E.; Fletcher, Evan; Singh, Baljeet; Floriolli, David; Kawas, Claudia H.; Fisher, Mark J. (Frontiers in Aging Neuroscience, 2019)
Purpose: To analyze the relationship between blood pressure (BP) variables, including circadian pattern, and cognition in 90+ year-olds. Methods: Twenty-four hour ambulatory BP monitoring was completed on 121 participants drawn from a longitudinal study of aging and dementia in the oldest-old. Various measures of BP and its variability, including nocturnal dipping, were calculated. Each person was given both a neuropsychological test battery covering different cognitive domains and a neurological examination to determine cognitive status. Seventy-one participants had a brain magnetic resonance imaging (MRI) scan. Results: Participants ranged in age from 90 to 102 years (mean = 93), about two-thirds were female, and nearly 80% had at least some college education. Mean nocturnal dips differed significantly between cognitively normal (n = 97) and impaired individuals (n = 24), with cognitively normal participants having on average greater nocturnal dips [6.6% vs. 1.3%, p = 0.006 for systolic BP (SBP); 11% vs. 4.4%, p = 0.002 for diastolic BP (DBP)]. Nocturnal dips were also related to performance on select cognitive test scores (especially those related to language, recent memory and visual-spatial ability), with individuals who performed below previously established median norms having significantly smaller nocturnal dips (both SBP and DBP) than those above the median. DBP reverse dippers had larger mean white matter hyperintensities (WMH as percent of total brain volume; 1.7% vs. 1.2%, 1.1% and 1.0% in extreme dippers, dippers, non-dippers) and a greater proportion had lobar cerebral microbleeds (CMBs; 44% vs. 0%, 7%, 16%, p < 0.05). Impaired participants had higher mean WMH than those with normal cognition (1.6% vs. 1.0% p = 0.03) and more tended to have CMB (31% vs. 20%, p = n.s.). Conclusion: These findings suggest that cognitive dysfunction is associated with dysregulation in the normal circadian BP pattern. Further study is warranted of the potential role of WHM and CMB as mediators of this association.